2021
DOI: 10.4240/wjgs.v13.i4.330
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal compartment syndrome among surgical patients

Abstract: Abdominal compartment syndrome (ACS) develops when organ failure arises secondary to an increase in intraabdominal pressure. The abdominal pressure is determined by multiple factors such as blood pressure, abdominal compliance, and other factors that exert a constant pressure within the abdominal cavity. Several conditions in the critically ill may increase abdominal pressure compromising organ perfusion that may lead to renal and respiratory dysfunction. Among surgical and trauma patients, aggressive fluid re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 44 publications
(50 reference statements)
0
12
0
1
Order By: Relevance
“…Since the abnormal abdominal pressure itself impairs organ perfusion, it results in a vicious circle. This cycle can be broken by decompression by emergency laparotomy and open abdomen treatment [25] .…”
Section: Step 4: Surgical Therapy Of Vitt-associated Acute Portal Vei...mentioning
confidence: 99%
“…Since the abnormal abdominal pressure itself impairs organ perfusion, it results in a vicious circle. This cycle can be broken by decompression by emergency laparotomy and open abdomen treatment [25] .…”
Section: Step 4: Surgical Therapy Of Vitt-associated Acute Portal Vei...mentioning
confidence: 99%
“…In addition to controlling intravascular volume, intraluminal volume should be reduced by the use of nasogastric and rectal tubes for decompression. Prokinetic agents may be preferred in selected cases with gastroparesis and non-mechanical ileus [57].…”
Section: Enteral Managementmentioning
confidence: 99%
“…IAH is more likely to develop in all abdominal trauma patients. 12 Findings of a case control study concluded that without a pre-operative blood pressure of at least 70 mmHg, the requirement for an aortic occlusion balloon, or the necessity for more than five intra-operative red blood cell unit transfusions, there is a low likelihood that ACS after endovascular aneurysm repair will occur. ACS is mostly related to physiological parameters.…”
Section: Risk Factors For Acsmentioning
confidence: 99%